Artificial intelligence in medicine : technical basis and clinical applications - Xing, Lei; Giger, Maryellen Lissak, 1956-; Min, James K. (Academic Press, 2021)
Artificial Intelligence in Medicine: Technical Basis and Clinical Applications presents a comprehensive overview of the field, ranging from its history and technical foundations, to specific clinical applications and finally to prospects. Artificial intelligence (AI) is expanding across all domains at a breakneck speed. The field of medicine, with its availability of large multidimensional datasets, lends itself to strong potential advancement with the appropriate harnessing of AI. AI also provides the opportunity to improve upon research methodologies beyond what is currently available using traditional statistical approaches.